2018
DOI: 10.1002/cssc.201801321
|View full text |Cite
|
Sign up to set email alerts
|

Ion Dynamics in Ionic‐Liquid‐Based Li‐Ion Electrolytes Investigated by Neutron Scattering and Dielectric Spectroscopy

Abstract: A detailed understanding of the diffusion mechanisms of ions in pure and doped ionic liquids remains an important aspect in the design of new ionic-liquid electrolytes for energy storage. To gain more insight into the widely used imidazolium-based ionic liquids, the relationship between viscosity, ionic conductivity, diffusion coefficients, and reorientational dynamics in the ionic liquid 3-methyl-1-methylimidazolium bis(trifluoromethanesulfonyl)imide (DMIM-TFSI) with and without lithium bis(trifluoromethanesu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 92 publications
3
24
0
Order By: Relevance
“…In the equimolar complexes of Li[TFSA] and G3 or G4 (so-called solvate ionic liquids), D Li is found to be identical to D sol , indicating that long-lived Li complex ions are formed due to the strongly chelating properties of G3 and G4. 32 Nevertheless, in the glyme-Li salt solvate ionic liquids, the Li ion transport can generally be interpreted as being via the physical diffusion mechanism that premises the translational motion of the solvated ions in a similar manner to that for ionic liquids 34 as well as dilute electrolyte solutions. 29 In contrast to these examples, the diffusion behavior observed for the highly concentrated Li[FSA]/keto ester systems is more akin to our recently published observations for SL-based concentrated electrolytes.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…In the equimolar complexes of Li[TFSA] and G3 or G4 (so-called solvate ionic liquids), D Li is found to be identical to D sol , indicating that long-lived Li complex ions are formed due to the strongly chelating properties of G3 and G4. 32 Nevertheless, in the glyme-Li salt solvate ionic liquids, the Li ion transport can generally be interpreted as being via the physical diffusion mechanism that premises the translational motion of the solvated ions in a similar manner to that for ionic liquids 34 as well as dilute electrolyte solutions. 29 In contrast to these examples, the diffusion behavior observed for the highly concentrated Li[FSA]/keto ester systems is more akin to our recently published observations for SL-based concentrated electrolytes.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…Ionic liquids (ILs) with favorable properties such as low vapor pressure, low flammability, wide electrochemical stability windows, and high ionic conductivities have been extensively investigated as electrolytes for electric energy storage applications, mainly with lithium‐ion batteries (LIBs) and sodium‐ion batteries (SIBs). [ 1–6 ] The successful operation of LIBs and SIBs, particularly their long term cycling stability, depends on the quality of solid electrolyte interphases (SEIs) formed on the surfaces of both anode and cathode electrodes (or cathode electrolyte interphase (CEI), in the case of the cathode). Both the SEI and CEI are ionically conductive but electronically insulative and mainly formed during the initial battery formation cycles.…”
Section: Introductionmentioning
confidence: 99%
“…For ionic liquids QENS has revealed a complex picture of the dynamics with several different processes contributing to the local dynamics. [27][28][29][30][31][32] However, to the best of our knowledge no studies have been reported on the local dynamics in highly concentrated electrolytes using QENS.…”
Section: Introductionmentioning
confidence: 99%